2007
DOI: 10.1161/strokeaha.106.467290
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated Hemoglobin Reduces the Size of Cerebral Infarction in the Rat

Abstract: Background and Purpose-Liposome-encapsulated hemoglobin (LEH; TRM-645) is a novel oxygen (O 2 ) carrier with a lower O 2 affinity (P 50 O 2 ϭ40 mm Hg) than red blood cells. In contrast to cell-free hemoglobin, encapsulation prevents hemoglobin extravasation, whereas its subcellular size (230 nm) may improve O 2 delivery and limit the severity of cerebral infarction. Methods-The extent of cerebral infarction was determined 24 hours after photochemically induced thrombosis of the middle cerebral artery from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 32 publications
(51 reference statements)
3
49
1
Order By: Relevance
“…Since LEH can deliver oxygen more efficiently to peripheral tissues because of its smaller diameter (200-250 nm; 1/40th the size of RBC), several studies have attempted to assess the therapeutic effects of LEH on brain ischemia. Intravenous administration of LEH reduced the extent of infarction in the cortex of a rat thrombotic MCAO model (Kawaguchi et al, 2007;Fukumoto et al, 2009) and in a nonhuman primate transient MCAO model (Kawaguchi et al, 2010). Another therapeutic effect of LEH on cognitive impairment was revealed in the analysis of hippocampal dysfunction after transient two-vessel or four-vessel occlusion (Kakehata et al, 2007;Hamadate et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Since LEH can deliver oxygen more efficiently to peripheral tissues because of its smaller diameter (200-250 nm; 1/40th the size of RBC), several studies have attempted to assess the therapeutic effects of LEH on brain ischemia. Intravenous administration of LEH reduced the extent of infarction in the cortex of a rat thrombotic MCAO model (Kawaguchi et al, 2007;Fukumoto et al, 2009) and in a nonhuman primate transient MCAO model (Kawaguchi et al, 2010). Another therapeutic effect of LEH on cognitive impairment was revealed in the analysis of hippocampal dysfunction after transient two-vessel or four-vessel occlusion (Kakehata et al, 2007;Hamadate et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported in the literature suggest the efficacy of Hb liposomes in the treatment of stroke by enhancing the biodistribution of Hb liposomes within the ischemic area in the brain. 144,145,147,[160][161][162][163][164]167,171,191,193,194 In the same way, liposomes for the delivery of angiogenic peptides 140 and VEGF 157 to promote angiogenesis in ischemic tissue were developed, and both formulations effectively promoted vascular regeneration. 140,157 Over the years, many liposomal formulations have been developed for the treatment of stroke.…”
Section: Stroke or Cerebral Ischemiamentioning
confidence: 99%
“…LEH reduced the size of cerebral infarction in rats subjected to photochemically induced thrombosis (PIT) of the middle cerebral artery (MCA) (6,7) and also in primates treated with MCA occlusion (MCAO) (8). Transfusion of LEH rescued lethal progressive hemodilution and improved hemodilution-induced metabolic acidosis in rats (9).…”
Section: Introductionmentioning
confidence: 99%